The Effect of Medium Chain Triglycerides on Time to Nutritional Ketosis and Symptoms of Keto-Induction in Healthy Adults: A Randomised Controlled Clinical Trial - Cliff J. d C. Harvey; Grant M. Schofield; Micalla Williden; Joseph A. McQuillan (Journal of Nutrition and Metabolism)
Medium chain triglycerides (MCTs) are ketogenic and might reduce adverse effects of keto-induction and improve time to ketosis and the tolerability of very low carbohydrate diets. This study investigates whether MCT supplementation improves time to nutritional ketosis (NK), mood, and symptoms of keto-induction. We compared changes in beta-hydroxybutyrate (BOHB), blood glucose, symptoms of keto-induction, and mood disturbance, in 28 healthy adults prescribed a ketogenic diet, randomised to receive either 30 ml of MCT, or sunflower oil as a control, three times per day, for 20 days. The primary outcome measured was the achievement of NK (≥0.5 mmol·L−1 BOHB). Participants also completed a daily Profile of Mood States and keto-induction symptom questionnaire. MCT resulted in higher BOHB at all time points and faster time to NK, a result that failed to reach significance. Symptoms of keto-induction resulted from both diets, with a greater magnitude in the control group, except for abdominal pain, which occurred with greater frequency and severity in the MCT-supplemented diet. There was a possibly beneficial effect on symptoms by MCT, but the effect on mood was unclear. Based on these results, MCTs increase BOHB compared with LCT and reduce symptoms of keto-induction. It is unclear whether MCTs significantly improve mood or time to NK. The trial was registered by the Australia New Zealand Clinical Trial Registry ACTRN12616001099415.